PERANCANGAN APLIKASI RUTE ANGKUTAN UMUM DI BOYOLALI BERBASIS ANDROID SMARTPHONE (STUDY KASUS Dinas Perhubungan Kabupaten Boyolali) - Titik Rochani; Saiful Bahri; Dwi Kristiani (JITU : Journal Informatic Technology And Communication, 2018)
The Research titled “Designing Applications of The Public Transportation Route in Boyolali based Android Smartphone (Case Study Department of Transportation (Transportation Agency) Boyolali)”. Research carried out starting from the month of May until August 2016. The purpose of the research can help people find out information about public transportation. Development of the system used in this research is the methodology Spiral Model. The application design with Spiral Model has six stages. The six stages of system development, among others are a liaison stage, the stage of planning, risk analysis stage, stage engineering, stage construction and the release and evalution phase. The results of this research is application based public transport service android that provides information to the user. In the application there are features that helps users know these Boyolali public transportation in the city.